Efficacy of intranasal LaAg vaccine against Leishmania amazonensis infection in partially resistant C57Bl/6 mice. Issue 1 (December 2016) - Pratti, Juliana; Ramos, Tadeu; Pereira, Joyce; da Fonseca-Martins, Alessandra; Maciel-Oliveira, Diogo; Oliveira-Silva, Gabriel; de Mello, Mirian; Chaves, Suzana; Gomes, Daniel; Diaz, Bruno; Rossi-Bergmann, Bartira; de Matos Guedes, Herbert
Abstract Background We have previously demonstrated that intranasal vaccination of highly susceptible BALB/c mice with wholeLeishmania amazonensis antigens (LaAg) leads to protection against murine cutaneous leishmaniasis. Here, we evaluate the response of partially resistant C57BL/6 mice to vaccination as a more representative experimental model of human cutaneous leishmaniasis. Methods C57BL/6 mice from different animal facilities were infected withL. amazonensis (Josefa strain) to establish the profile of infection. Intranasal vaccination was performed before the infection challenge with two doses of 10 μg of LaAg alone or associated with the adjuvant ADDAVAX® by instillation in the nostrils. The lesion progression was measured with a dial caliper and the parasite load by limited dilution assay in the acute and chronic phases of infection. Cytokines were quantified by ELISA in the homogenates of infected footpads. Results C57BL/6 mice from different animal facilities presented the sameL. amazonensis infection profile, displaying a progressive acute phase followed by a controlled chronic phase. Parasites cultured in M199 and Schneider's media were equally infective. Intranasal vaccination with LaAg led to milder acute and chronic phases of the disease. The mechanism of protection was associated with increased production of IFN-gamma in the infected tissue as measured in the acute phase. Association with the ADDAVAX® adjuvant did not improve the efficacy of intranasal LaAg vaccination. Rather, ADDAVAX® reduced vaccination efficacy. Conclusion This study demonstrates that the efficacy of adjuvant-free intranasal vaccination with LaAg is extendable to the more resistant C57Bl/6 mouse model of infection withL. amazonensis, and is thus not exclusive to the susceptible BALB/c model. These results imply that mucosal immunomodulation by LaAg leads to peripheral protection irrespective of the genetic background of the host.